Ensuring Certainty through Legal Reasoning: What Can Indonesia Learn from the United Kingdom and the Unites States? - Herliana, Herliana (Universitas Muhammadiyah Surakarta, 2023)
Purpose of the study : This study analyzes the principle and methodologies of legal reasoning by judges in the United Kingdom and the United States. Legal reasoning ensures legal certainty by promoting consistency, predictability, transparency, and adherence to legal principles and precedents. Legal reasoning provides a structured and principled approach to judicial decision making. The Indonesian legal system which predominantly follows a civil law tradition, stands to gain valuable insights from these common law models. Learning from common law models of legal reasoning can be used to overcome the existing problems with Indonesian judgment which considered to be lacking legal certainty. Methodology: This study is primarily normative legal research design to analyze and contrast legal reasoning practices in the United Kingdom and the United States. Results : This paper finds that elements of common law legal reasoning that can be implemented in Indonesia are the requirement for judge to provide ratio decidendi and obiter dicta in the court decision. The lesson Indonesia can learn from legal reasoning done by judges in the UK and the US are that Indonesian judges should not put the parties’ argument in their decision. Rather, the judges only need to focus on their own reason to be written in the judgment. In addition, Indonesian judges should not be too formalistic as this can result in a strict law enforcement without considering broader policy considerations or context. This paper posits that Indonesia's path to legal certainty lies in the consistency of legal reasoning in court judgment. The experiences of the United Kingdom and the United States, when thoughtfully adapted, promise a brighter future for Indonesian judiciary in which legal certainty thrives and justice prevails. Applications of this study : This analysis can provide insight into how the UK and the US that follow a common law system approach, provide takeaways or lessons that Indonesia can apply in order to ensure the principle of legal uncertainty. Novelty/ Originality of this study: This research offers a novel point of view on how the problem of lack of legal certainty in Indonesian judiciary can be overcome by implementing elements in the common law system. The author did not find any studies which use the United Kingdom and the United States approaches to legal reasoning as case studies to be learned from when Indonesia is about to ensure legal certainty. Therefore, this research provide a novelty in the field of Jurisprudence. ABSTRAK Tujuan: Tujuan penlitian ini adalah menganalisis asas dan metodologi penalaran hukum yang dilakukan oleh hakim di Inggris dan Amerika Serikat. Penalaran hukum merupakan unsur yang penting dalam kepastian hukum karena dengan penalaran putusan hakim dapat memberikan konsistensi dan prediktabilitas, transparansi dan kepatuhan terhadap asas hukum dan yurisprudensi. Penalaran hukum memberikan panduan structural dalam putusan hakim. Sistem hukum Indonesia yang mengikuti civil law system dapat mengambil manfaat dari common law system yang berlau di Inggris dan Amerika Serikat. Dengan mempelajari system di dua negara tersebut, penalaran hukum dapat digunakan untuk mengatasi masalah kurnagnya kepastian hukum di Indonesia. Metodologi: Penelitian ini adalah penelitian hukum normative yang didesain untuk menganalisis dan membandingkan praktek penalaran hukum di Inggris dan Amerika Serikat. Temuan: Hasil penelitian ini menunjukkan bahwa elemen dari penalaran hukum di system common law yang dapat diterapkan di Indonesia adalah keharusan bagi hakim untuk mencantumkan ratio decidendi dan obitur dicta. Pelajaran yang dapat diambil oleh Indonesia dari penalaran hukum di Inggris dan Amerika Serikat adalah bahwa putusan hakim tidak perlu memuat argumen para pihak secara keseluruhan karena hakim seharusnya fokus pada penalaran hukum, memberikan argumentasinya sendiri. Selain itu, dalam memutus perkara, hakim tidak bersikap terlalu formalistik karena hal itu akan mengesampingkan konteks perkara dan pertimbangan lain. Hal ini akan memberikan kepastian hukum. Penelitian ini menunjukkan bahwa apabila Indonesia ingin mewujudkan kepastian hukum salah satunya dapat dicapai melalui penalaran hukum. Pengalama Inggris dan Amerika Serikat bila diterapkan dapat memberikan masa depan yang lebih baik bagi penegakan hukum di Indonesia dimana kepastian dan keadilan hukum dijunjung tinggi. Kata kunci: Kepastian hukum, Penalaran hukum, system common law, system civil law